2019
DOI: 10.1021/acs.orglett.9b01307
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)-Catalyzed Enantioselective Hydroacylation of Racemic Allenals via Dynamic Kinetic Resolution

Abstract: Rhodium­(I)-catalyzed enantioselective hydroacylation of 4-allenals was found to proceed smoothly, giving six-membered ketones in good yields (up to 84% yield) with high enantiomeric excess (up to 96% ee) even from racemic allenes as substrates. Mechanistic studies revealed that racemization of the allene moiety in the substrate would occur via a dynamic kinetic resolution (DKR) process during the hydroacylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Among various alkylation strategies, direct α-addition to unsaturated alkenes or alkynes represents one of the most desirable processes due to its high atom-efficiency . Recent advances in asymmetric catalysis have enabled the α-coupling of carbonyls with conjugated dienes, allenes, and even simple alkenes . Alkynes bearing terminal propyne units have also been explored in the asymmetric α-alkylation of carbonyls .…”
mentioning
confidence: 99%
“…Among various alkylation strategies, direct α-addition to unsaturated alkenes or alkynes represents one of the most desirable processes due to its high atom-efficiency . Recent advances in asymmetric catalysis have enabled the α-coupling of carbonyls with conjugated dienes, allenes, and even simple alkenes . Alkynes bearing terminal propyne units have also been explored in the asymmetric α-alkylation of carbonyls .…”
mentioning
confidence: 99%
“…While 1:1 coupling (hydroacylation) reactions between aldehydes and alkenes or alkynes have been most extensively developed in both intramolecular and intermolecular settings, allenes have also attracted significant interest as unique reaction partners for aldehydes. Thus, rhodium-catalyzed hydroacylation reactions of allenes using chelating aldehydes such as salicylaldehyde and methylthio-substituted aldehyde have been reported by groups led by Miura and Willis, respectively, the latter being achieved in an enantioselective fashion . Dong and co-workers achieved ruthenium-catalyzed hydroacylation of alkynes with simple aromatic aldehydes, which involves in situ generation of allenes from the alkynes .…”
mentioning
confidence: 99%
“…Thus, rhodium-catalyzed hydroacylation reactions of allenes using chelating aldehydes such as salicylaldehyde and methylthiosubstituted aldehyde have been reported by groups led by Miura 2 and Willis, 3 respectively, the latter being achieved in an enantioselective fashion. 4 Dong and co-workers achieved ruthenium-catalyzed hydroacylation of alkynes with simple aromatic aldehydes, which involves in situ generation of allenes from the alkynes. 5 Besides the 1:1 coupling reactions, a few examples of aldehyde/allene coupling engaging an extra πsubstrate have been reported.…”
mentioning
confidence: 99%
“…In recent years, metal-catalyzed functional grouping of allenes to synthesize various heterocyclic compounds has become a research hotspot. In particular, the study of pyrazoline compounds remains a challenge for researchers. In our study on allene chemistry, we have demonstrated that allenes with nucleophilic functional groups are common building blocks for the synthesis of potentially important heterocyclic compounds, such as imidazolidines .…”
mentioning
confidence: 99%
“…On the basis of previous research, we propose a possible reaction mechanism in Scheme . Initially, Pd(0) reacts with the aryl iodide to give oxidative addition product A .…”
mentioning
confidence: 99%